INFLUENCE OF THE CHINESE LOAN WORDS USED IN KAZAKH LANGUAGE (International relations and international law Journal, 2016)
In the article  author investigates a question of influence of the Chinese loan words used in Kazakh language.
Keywords: loan words; kazakh language